The accuracy and the honesty while the recklessness and the negligence in the practice of the family doctor - Trnka, Jakub; Drobnik, Jarosław; Susło, Robert; Steciwko, Andrzej (Przewodnik Lekarza/Guide for GPs, 2008)
Accuracy and honesty in the patient treatment constitutes main rules in all medical practitioners’ work. The educational efforts are aimed at teaching young medical practitioners, except of outlines of the current medical knowledge, also rules of proper and honest proceeding with patients. Recklessness and negligence contrast them and often threat the patient with unpleasant consequences. In such cases medical practitioners bear the responsibility of various kinds: criminal, civil, professional and official. Several examples of the negligence in the course of professional activities of medical practitioners mentioned illustrate various ways medical errors can be made.